(3EQTGO GdbGUO Edi CSfi GdebGUOs - (3eMeO Hf EHQGgje Hf SGYO GdGfUGQj GdSfLGQj, hjYQa HGHf GdCcaGfj, CHh YHO Gddg,J (B749 (3g` s
(3ChdgG (B:s
(3hHYO aEf HfG MGLI Edi Jcejd fahSfG GdHTQjI ai bhGgG GdfXQjI hGdYedjI s
(3HBNQgG fHPI ai KdGK UaMGJ ai JdNjU NGJeI GdcJGH fbdkG Yf fSNI GdeDdas
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B299 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B200s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B137 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B169 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeg (B- (3U (B79 s
Keywords: (3GdeYGQa GdYGeIs